Nutrient limitation of alpine plants: Implications from leaf N : P stoichiometry and leaf δ15N. Issue 3 (19th February 2014) - Xu, Xingliang; Wanek, Wolfgang; Zhou, Caiping; Richter, Andreas; Song, Minghua; Cao, Guangmin; Ouyang, Hua; Kuzyakov, Yakov
Abstract: Nitrogen (N) deposition can affect grassland ecosystems by altering biomass production, plant species composition and abundance. Therefore, a better understanding of the response of dominant plant species to N input is a prerequisite for accurate prediction of future changes and interactions within plant communities. We evaluated the response of seven dominant plant species on the Tibetan Plateau to N input at two levels: individual species and plant functional group. This was achieved by assessing leaf N : P stoichiometry, leaf δ 15 N and biomass production for the plant functional groups. Seven dominant plant species—three legumes, two forbs, one grass, one sedge—were analyzed for N, P, and δ 15 N 2 years after fertilization with one of the three N forms: NO$ _3^- $, NH$ _4^+ $, or NH4 NO3 at four application rates (0, 7.5, 30, and 150 kg N ha –1 y –1 ). On the basis of biomass production and leaf N : P ratios, we concluded that grasses were limited by available N or co‐limited by available P. Unlike for grasses, leaf N : P and biomass production were not suitable indicators of N limitation for legumes and forbs in alpine meadows. The poor performance of legumes under high N fertilization was mainly due to strong competition with grasses. The total above‐ground biomass was not increased by N fertilization. However, species composition shifted to more productive grasses. A significant negative correlation between leaf N : P and leaf δ 15 N indicated that the two forbs Gentiana straminea and Saussurea superba switched from N deficiency to P limitation ( e.g., N excess) due to N fertilization. These findings imply that alpine meadows will be more dominated by grasses under increased atmospheric N deposition.